1,000 inventions & discoveries - Bridgman, Roger Francis, 1940- (London ; New York : DK Pub. ; [Washington, D.C.] : in association with the Smithsonian Institution, 2002)
Summarizes 100 notable inventions and discoveries of ancient and modern times, from 3,000,000 B.C. to the beginning of the twenty-first century A.D.
Fakulti Teknologi Kreatif Dan Warisan
Includes bibliographical references (p. 256) and index.
Keywords: Inventions -- History; Inventions -- History -- Juvenile literature